メタ認知を促す医学教育 - 下島 裕美; 三浦 雅文; 門馬 博; 齋藤 昭彦; 蒲生 忍 (JOURNAL OF THE KYORIN MEDICAL SOCIETY, 2015)
A medical team consist of various professionals―physicians, nurses, clinical laboratory technicians, physiotherapists, occupational therapists, clinical engineers, radiological technicians, pharmacists, caregivers, and social welfare workers. Furthermore, patients and their families have the right to participate in determining the patient’s therapeutic process. For medical professionals with various values to function as a team that provides therapy to a single patient, they must be aware of the commonalities and discrepancies between their perspectives and those of others. They must seek to make the best decision for the patient from a panoramic perspective. When teaching this panoramic perspective, the concept known in psychology as metacognition might be effective. Therefore, this study discusses the four-box method for decision making in medical ethics from the viewpoint of metacognition and proposes the effect of the metacognition education in an individual level and a group level, and the effect of the metacognition education in expertise. 医療チームは，医師，看護師，臨床検査技師，理学療法士，作業療法士，臨床工学士，放射線技師，薬剤師，介護士，社会福祉士など多様な職種から構成される。更には患者とその家族もまた自身の治療プロセスの決定に参加する権利を持っている。多様な価値観をもった人々が一つのチームとして一人の患者の治療にあたるためには，自分の視点と他者の視点の共通点・相違点を認識した上で，患者にとって最善の意思決定を俯瞰的な視点で追及する姿勢が必要であろう。この俯瞰的な視点の教育には，心理学におけるメタ認知と呼ばれる概念が有効であると考えられる。そこで本論文では，医療倫理における意思決定を促進する方法である4ボックス法（4 box method, 四分割法）をメタ認知という視点から考察する。個人レベルと集団レベルにおけるメタ認知教育の効果と，熟達化におけるメタ認知教育の効果を提案する。